2020
DOI: 10.1101/2020.05.04.077024
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tyrosine kinase inhibitors induce mitochondrial dysfunction during cardiomyocyte differentiation through alteration of GATA4-mediated networks

Abstract: SUMMARYMaternal drug exposure during pregnancy increases the risks of developmental cardiotoxicity, leading to congenital heart defects (CHDs). In this study, we used human stem cells as an in-vitro system to interrogate the mechanisms underlying drug-induced toxicity during cardiomyocyte differentiation, including anticancer tyrosine kinase inhibitor (TKI) drugs (imatinib, sunitinib, and vandetanib). H1-ESCs were treated with these drugs at sublethal levels during cardiomyocyte differentiation. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…Previous evidence indicates PGC-1α as a central regulator of cardiac metabolism and promoter of oxidative phosphorylation at the expense of glycolysis [77,78]. Whereas AMPK upregulation leads to improved mitochondrial activity and homeostasis in cardiomyocytes [79][80][81][82]. We found that AA-treated iPSC-CMs have undergone significant metabolic changes; genes responsible for the electron transport chain, oxidative phosphorylation, and fatty acid β-oxidation in mitochondria (NDUFV3, COX3, and COX5B) were highly expressed (Additional file 1: Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence indicates PGC-1α as a central regulator of cardiac metabolism and promoter of oxidative phosphorylation at the expense of glycolysis [77,78]. Whereas AMPK upregulation leads to improved mitochondrial activity and homeostasis in cardiomyocytes [79][80][81][82]. We found that AA-treated iPSC-CMs have undergone significant metabolic changes; genes responsible for the electron transport chain, oxidative phosphorylation, and fatty acid β-oxidation in mitochondria (NDUFV3, COX3, and COX5B) were highly expressed (Additional file 1: Fig.…”
Section: Discussionmentioning
confidence: 99%